The trade-off between inflation and unemployment in an MMT world: An open economy perspective - Emilio Carnevali; Matteo Deleidi (Levy Economics Institute of Bard College, 2020)
This paper is focused on Modern Monetary Theory's (MMT) treatment of inflation from an open economy perspective. It analyzes how the inflation process is explained within the MMT framework and provides empirical evidence in support of this vision. However, it also makes use of a stock-flow consistent (open economy) model to underline some limits of the theory when it is applied in the context of a non-US (relatively) open economy with a flexible exchange rate regime. The model challenges the contention made by MMTers that measures such as the job guarantee program can achieve full employment without facing an inflation-unemployment trade-off.
Keywords: E51; E12; F41; 330; Central Banking; Post-Keynesian; Open Economy Model; Modern Money Theory